2017
DOI: 10.1177/0894845317731157
|View full text |Cite
|
Sign up to set email alerts
|

Career, Family, and Workforce Mobility: An Interdisciplinary Conversation

Abstract: The purpose of this article is to synthesise conceptual and empirical work from the fields of both sociology and career development to explore how issues of career, family and workforce mobility are necessarily interrelated. The use of work from sociology and career development demonstrates that the complexities of family solutions to career mobility undo the apparent simplicity of delivering a worker to a new worksite. Although organizations and governments work to develop policies that incentivize mobility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Liu et al 2020;Whiston and Keller 2004). This also supports previous research that has identified family related antecedents of mobility decisions (Gripenberg et al 2013;Mutter 2017;Patton and Doherty 2017;Tarique and Weisbord 2013).…”
Section: Understanding Geographic Mobility Readinesssupporting
confidence: 77%
“…Liu et al 2020;Whiston and Keller 2004). This also supports previous research that has identified family related antecedents of mobility decisions (Gripenberg et al 2013;Mutter 2017;Patton and Doherty 2017;Tarique and Weisbord 2013).…”
Section: Understanding Geographic Mobility Readinesssupporting
confidence: 77%
“…Five articles included in this special issue consider the role of individual differences in one’s career growth. The first article, by Patton and Doherty (2019), introduces family issues as a personal factor that can affect career growth. This article discusses how family issues can facilitate or undermine attempts to transfer an employee to a new location.…”
Section: Is Individual Career Growth Related To Demographic Personalmentioning
confidence: 99%
“…Two articles in this issue further improve our understanding of the mechanisms behind upward career mobility. First, considering the increasing career opportunities brought by mobility, Patton and Doherty (2019) focus on career mobility between organizations. They explore the complexity of career mobility with an emphasis on family situations.…”
Section: Why Do Some Individuals Experience More Successful Career Momentioning
confidence: 99%
See 1 more Smart Citation
“…However, while married women enjoyed the privilege of social approval in ways that single women did not, gender appeared to always supersede the privileges awarded by marriage. Some married women in our sample noted that the simultaneous career pursuit of both themselves and their partners involved strategic decision-making in order to navigate the family and mobility demands of dual-career couples (Patton and Doherty, 2017). This resulted in challenges for the women in cases where they travelled first to the Middle East; for example, one participant noted that she moved first with her small children to secure accommodation, register the children at a school and undertake other tasks associated with setting up home in Qatar, while her spouse dealt with the sale of the family home and the logistics of household relocation.…”
Section: Empirical Findings: Navigating Privilege and Disadvantage Inmentioning
confidence: 99%